Joseph L. Rauh papers - Rauh, Joseph L., 1911-
Chiefly legal files together with correspondence, memoranda, minutes of meetings, oral history interviews, speeches, writings, subject files, appointment books, and other papers relating to Rauh's career as a public interest lawyer handling cases pertaining to civil rights, civil liberties, and labor disputes. Includes files relating to his activities with Americans for Democratic Action and to his participation in Hubert H. Humphrey's presidential campaign in 1960. Subjects include affirmative action, foreign and domestic policy, liberalism, the Democratic party, politics, national political campaigns, Senate filibuster, home rule for the District of Columbia, the U.S. Supreme Court, rights of trade unions, government loyalty/security measures, communism, the House Committee on Un-American Activities, and the Vietnamese conflict.
Clients represented include the Brotherhood of Sleeping Car Porters, Lillian Hellman, International Union, United Automobile Workers of America, Mississippi Freedom Democratic Party, and Velma (Mrs. David) Orlikow. Correspondents include Carl A. Auerbach, William J. Brennan, Benjamin N. Cardozo, Benjamin V. Cohen, Paul Howard Douglas, Felix Frankfurter, Jack Greenberg, Aaron Henry, Edward D. Hollander, Hubert H. Humphrey, Lyndon B. Johnson, Edward Moore Kennedy, James I. Loeb, Eugene J. McCarthy, Walter Reuther, Eleanor Roosevelt, Arthur Meier Schlesinger, Jr., James Arthur Wechsler, Roy Wilkins, and Joseph Yablonski. Includes a letter from Arthur Miller describing his reaction to Marilyn Monroe's death.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Lawyer, civil rights activist, and civil libertarian of Washington, D.C. Born Joseph Louis Rauh, Jr. Died 1992.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Auerbach, Carl A. -- 1915- -- Correspondence; Brennan, William J. -- 1906-1997 -- Correspondence; Cardozo, Benjamin N. -- 1870-1938 -- Correspondence; Cohen, Benjamin V. -- Correspondence; Douglas, Paul H. -- 1892-1976 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Greenberg, Jack, -- 1924- -- Correspondence; Hellman, Lillian, -- 1905-1984 -- Correspondence; Henry, Aaron, -- 1922-1997 -- Correspondence; Hollander, Edward D. -- 1908- -- Correspondence; Humphrey, Hubert H. -- 1911-1978.; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kennedy, Edward M. -- 1932-2009 -- Correspondence; Loeb, James I. -- 1908- -- Correspondence; McCarthy, Eugene J., -- 1916-2005 -- Correspondence; Miller, Arthur, -- 1915-2005 -- Correspondence; Monroe, Marilyn, -- 1926-1962.; Orlikow, Velma; Reuther, Walter, -- 1907-1970 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Schlesinger, Arthur M. -- 1917-2007 -- Correspondence; Wechsler, James A. -- 1915-1983 -- Correspondence; Wilkins, Roy, -- 1901-1981 -- Correspondence; Yablonski, Joseph A. -- 1941- -- Correspondence; United States. -- Congress. -- House. -- Committee on Un-American Activities; United States. -- Supreme Court; Americans for Democratic Action; Brotherhood of Sleeping Car Porters; Democratic Party (U.S.); International Union, United Automobile Workers of America (A.F. of L.); International Union, United Automobile Workers of America (CIO); Mississippi Freedom Democratic Party; Affirmative action programs -- United States; Automobile industry workers -- Labor unions; Civil rights -- United States; Communism; Filibusters (Political science) -- United States; Labor disputes -- United States; Labor unions -- United States; Liberalism -- United States; National security -- United States; Patriotism -- United States; Political campaigns -- United States; Political parties -- Mississippi; Practice of law -- Washington (D.C.); Public interest law -- United States; Vietnam War, 1961-1975.; Mississippi -- Politics and government -- 1951-; United States -- Economic policy -- 20th century; United States -- Foreign relations -- 20th century; United States -- Politics and government -- 20th century; Washington (D.C.) -- Politics and government; Civil libertarians; Civil rights leaders; Lawyers